Testimony from the Nazi Camps - Hutton, Margaret Anne (Routledge Studies in Twentieth-Century Literature, 2005)
This interdisciplinary study intergrates historiographical, literary and cultural methodologies in its focus on a little known corpus of testimonial accounts published by French women deported to Nazi camps. Comprising epistemological and literary analyses of the accounts and an examination of the construction of deportee identities, it will interest those working in the fields of modern French literature, genre, women's studies and the Holocaust.